ERAN SEMAR, GARENG, DAN PETRUK DALAM PERTUNJUKAN WAYANG KULIT PALEMBANG LAKON PRABU UKIR GELUNG NEGAK BLABAR KAWAT - J., Johansyah; I Nyoman Murtana (Lakon Jurnal Pengkajian & Penciptaan Wayang, 2015)
In responding to the cultural and traditional development in Palembang, the writer tries to analyzean interesting phenomena on wayang kulit performance in Palembang involving theater Dulmulukartists appointed by the dalang to take the roles of Semar, Gareng, and Petruk in lakon PrabuUkir gelung Negak Blabar Kawat. The research is analized by using the theories of dramaturgi,role, structure, and creativity. The data is collected by using descriptive analysis method. Thefinding shows that the performance gets a good respond from the audience because of thepresence of Semar, Gareng, and Petruk. Their presence in the performance has made achange to the performance structure and has given a good enthusiasm to the audience.Keywords: wayangkulit Palembang, Semar, Gareng, Petruk, role.